Food Next Door (FND): A Case Study on Empowering Home Chefs - Zokarkar, Uday; Sen, Subhasis (AMC Indian Journal of Entrepreneurship, 2024)
Purpose : The case study aimed to ascertain the marketing tactics that the two aspiring business owners should employ to ensure the success of FND, a meal delivery enterprise. Methodology : The case is based on a thorough examination of secondary data gathered from the FND website and research publications as well as primary data obtained from interviewing two aspiring business owners. Findings : The case study highlighted the significance of business transformation during lockdown and post-lockdown when different communities in India were seeking food as per their likings and habits. Practical Implications : Customers now use apps to order goods and services, completely altering the landscape of the company. This is the result of digital entrepreneurship. For all traditional enterprises turning to become digital marketplaces, COVID-19 served as a wake-up call. Originality : Using food delivery applications, marketing mix methods related to online services, and WhatsApp communities, two aspiring entrepreneurs under the name FND took on the issue of providing home-cooked food in Gujarat and projected their intentions for setting up a startup business.